2021
DOI: 10.5014/ajot.2021.044248
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Occupational Performance Scale of the Sensory Processing Three Dimensions Measure

Abstract: Importance: The Sensory Processing Three Dimensions (SP3D) Occupational Performance Scale (OPS) is a new parent-report measure developed for use as part of a comprehensive occupational therapy evaluation for children with sensory processing and integration challenges.Objective: To examine the internal consistency and discriminant validity of the SP3D OPS, examine relations between sensory processing subtypes and areas of occupational performance (OP), and determine the extent to which specific sensory processi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(24 reference statements)
1
1
0
Order By: Relevance
“…The protocol couples parent and adolescent goals in a unique form -parents are encouraged to set goals that amplify their specific role in advancing the adolescent goal; (3) the therapeutic relationship and communication were enhanced by continuously using the IRM model to respond to parent's needs during the session. These three active ingredients are consistent with the recommendations of Schoen et al (2021) for parental involvement in the assessment process, which should include a parent-therapist discussion regarding areas of concern in daily life. This process strives for a better understanding of the relationships between body functions and occupational performance in order to promote family-centered care and for determining meaningful intervention goals; (4) In the qualitative analysis of this study (Kahlon et al, 2023), Self Determination Theory (SDT; Ryan and Deci, 2017) was found to be an adequate theoretical framework that can help in understanding treatment outcomes.…”
Section: Discussionsupporting
confidence: 59%
“…The protocol couples parent and adolescent goals in a unique form -parents are encouraged to set goals that amplify their specific role in advancing the adolescent goal; (3) the therapeutic relationship and communication were enhanced by continuously using the IRM model to respond to parent's needs during the session. These three active ingredients are consistent with the recommendations of Schoen et al (2021) for parental involvement in the assessment process, which should include a parent-therapist discussion regarding areas of concern in daily life. This process strives for a better understanding of the relationships between body functions and occupational performance in order to promote family-centered care and for determining meaningful intervention goals; (4) In the qualitative analysis of this study (Kahlon et al, 2023), Self Determination Theory (SDT; Ryan and Deci, 2017) was found to be an adequate theoretical framework that can help in understanding treatment outcomes.…”
Section: Discussionsupporting
confidence: 59%
“…Sensory processing is defined as “the ability to manage detection, modulation, interpretation, and organization of incoming sensory information” [ 1 , 2 ]. Recently, there has been an explosion of interest in sensory processing, in part related to the addition of sensory responsivity to the diagnostic criteria of autism spectrum disorder (ASD) [ 3 ] and the increasing recognition that impairments in sensory processing, sometimes referred to as sensory processing disorder (SPD), affect everyday performance and participation [ 1 , 4 , 5 , 6 , 7 , 8 ]. Sensory processing includes both the ability to discriminate sensory information as well as the ability to modulate incoming sensory information.…”
Section: Introductionmentioning
confidence: 99%